EFEKTIFITAS LARUTAN TEMULAWAK (Curcuma xanthorrhiza Roxb.) TERHADAP PENINGKATAN JUMLAH LEUKOSIT AYAM BROILER (Gallus gallus Domestica sp.) - Irham Falahudin; elfira rosa pane; sugiati sugiati (Biota, 2016)
Temulawak (Curcuma xanthoriza Roxb.) is one of zingibereceae family medicinal plants that grow in Indonesia. Temulawak is a medicinal plant which also has a function as an immunomodulator. The present experiment was conducted in order to study the effect of temulawak extracts on the total of leucocytes in broiler chickens. The research was conducted in the Laboratory of Biology UIN Raden Fatah Palembang. The research was done by looking at the amount of the average increase before, 8 hours, and 22 days were treated with 3 replications. Twenty seven broiler chickens, 2 weeks old were used in this experiment, and were devided into 9 groups treatments, there were: (X0) negative control without the temulawak extract, (A1) 0,5 ml temulawak extract, (A2) 1 ml temulawak extract, (A3) 1,5 ml temulawak extract, (A4) 2 ml temulawak extract, (B1) 0,5 ml chemical antibiotics, (B2) 1 ml chemical antibiotics, (B3) 1,5 ml chemical antibiotics, (B4) chemical antibiotics. The observations showed an increase in the total of leucocytes after 8 hours of the treated solution A3 ginger in the treatment dose of 1,5 ml temulawak extract of 30016,5 μl and after 22 days treatment were given a solution of ginger at dose 1,5 temulawak extract of 29250 μl. In conclusion, temulawak extract has an activity as an immunostimulant for non specific immune response